1995
DOI: 10.1111/j.1365-3148.1995.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal anti‐D specificity and Rh D structure: criteria for selection of monoclonal anti‐D reagents for routine typing of patients and donors

Abstract: The Rh blood group system is the next most important to the ABO system in terms of its clinical significance in blood transfusion. It is vital to the safe, efficient practice of transfusion medicine that Rh D phenotyping tests are selected, executed and interpreted correctly. However, the Rh D blood group antigen has been shown to be subject to many phenotypic variations, and different reagents and typing techniques vary in their ability to detect these variants. The range of D-positive phenotypes are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 44 publications
2
61
0
2
Order By: Relevance
“…Serological analysis of DNU and D II phenotype erythrocytes with monoclonal anti-Ds of antiepD3, 4 and 9 specificity (nine-epitope model) reveal subtle differences in the expression of these epitopes (Table I). Our findings subsplit these epitopes (EpD3a/b, EpD4a/b, epD9a/ b), and are novel reaction profiles to those described by Jones et al (1995) (Table I). We have shown that the DNU phenotype arises by a single point mutation in the RHD gene, altering amino acid 353 (Gly → Arg).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Serological analysis of DNU and D II phenotype erythrocytes with monoclonal anti-Ds of antiepD3, 4 and 9 specificity (nine-epitope model) reveal subtle differences in the expression of these epitopes (Table I). Our findings subsplit these epitopes (EpD3a/b, EpD4a/b, epD9a/ b), and are novel reaction profiles to those described by Jones et al (1995) (Table I). We have shown that the DNU phenotype arises by a single point mutation in the RHD gene, altering amino acid 353 (Gly → Arg).…”
Section: Discussionsupporting
confidence: 70%
“…This observation, although localizing these residues to the predicted sixth external domain of the protein, is surprising inasmuch as almost all anti-epD3, 4 and 9 antibodies react strongly with bromelain treated D-positive erythrocytes ( Jones et al, 1995). It would appear that, following protease treatment of erythrocytes, the overall integrity of the sixth loop structure is maintained allowing recognition by antibodies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…ABO phenotypes and Rh factor evaluations were carried out by standard hemagglutination assays [36]. H. pylori positivity was assessed through H. pylori antigen rapid test device (feces) [37] or UBT [38].…”
Section: Methodsmentioning
confidence: 99%